IMPLEMENTATION OF PHATIC COMMUNICATION ON LEARNING THE DIGITAL ERA AT SMA IT IQRA' KOTA BENGKULU - Br Saragih, Rasiana; Badeni; Hadiwinarto (Corolla International Conference, 2022)
Learning in the digital era has different characteristics from learning in the past, where in this digital era the students are those who are classified as digital natives. Students are currently growing and developing in contact with digital technology, and this also has implications for learning activities carried out at school. The purpose of this study is to describe the implementation of phatic communication in PBM at SMA IT Iqra' Kota Bengkulu. Phatic communication is a communication situation that creates pleasure among communication participants. Phatic communication covers the entire scope of communication, including the scope of education, especially in the teaching and learning process. Of course, every student and teacher expects the learning situation to take place effectively and comfortably. As partners as facilitators, teachers must be able to design PBM activities to run well and achieve the goals set. Data was collected through observation and in-depth interviews as well as documentation studies. Besides having an effect on increasing enthusiasm and learning achievement, phatic communication also creates pleasure and comfort for both students and teachers. Through the application of phatic communication, individuals can learn love, compassion, intimacy, sympathy, respect, and empathy.